Electrical Crystallization Mechanism and Interface Characteristics of Nanowire ZnO/Al Structures Fabricated by the Solution Method. (3rd May 2012) - Tseng, Yi-Wei; Hung, Fei-Yi; Lui, Truan-Sheng; Chen, Yen-Ting; Xiao, Ren-Syuan; Chen, Kuan-Jen
Abstract : Both solution nanowire ZnO and sputtered Al thin film on SiO2 as the wire-film structure and the Al film were a conductive channel for electrical-induced crystallization (EIC). Direct current (DC) raised the temperature of the Al film and improved the crystallization of the nanostructure. The effects of EIC not only induced Al atomic interface diffusion, but also doped Al on the roots of ZnO wires to form aluminum doped zinc oxide (AZO)/ZnO wires. The Al doping concentration and the distance of the ZnO wire increased with increasing the electrical duration. Also, the electrical current-induced temperature was ~ 211°C (solid-state doped process) and so could be applied to low-temperature optoelectronic devices.